2018
DOI: 10.1016/j.dnarep.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Repair of exogenous DNA double-strand breaks promotes chromosome synapsis in SPO11-mutant mouse meiocytes, and is altered in the absence of HORMAD1

Abstract: Repair of SPO11-dependent DNA double-strand breaks (DSBs) via homologous recombination (HR) is essential for stable homologous chromosome pairing and synapsis during meiotic prophase. Here, we induced radiation-induced DSBs to study meiotic recombination and homologous chromosome pairing in mouse meiocytes in the absence of SPO11 activity (Spo11 model), and in the absence of both SPO11 and HORMAD1 (Spo11/Hormad1 dko). Within 30 min after 5 Gy irradiation of Spo11 mice, 140-160 DSB repair foci were detected, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 83 publications
3
39
0
Order By: Relevance
“…The new role we define for HORMAD1 in promoting DSB repair in cancer cells differs from how Hormad1 impacts repair radiation-induced DSB in mouse meiotic cells 50 . Carofiglio and colleagues examined repair kinetics of IR-induced DSB in Spo11/Hormad1 double knockout mice 50 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The new role we define for HORMAD1 in promoting DSB repair in cancer cells differs from how Hormad1 impacts repair radiation-induced DSB in mouse meiotic cells 50 . Carofiglio and colleagues examined repair kinetics of IR-induced DSB in Spo11/Hormad1 double knockout mice 50 .…”
Section: Discussionmentioning
confidence: 89%
“…The new role we define for HORMAD1 in promoting DSB repair in cancer cells differs from how Hormad1 impacts repair radiation-induced DSB in mouse meiotic cells 50 . Carofiglio and colleagues examined repair kinetics of IR-induced DSB in Spo11/Hormad1 double knockout mice 50 . Those workers observed fewer DSB repair foci remaining 24 h and 48 h after irradiation in Spo11 −/− /Hormad −/− double knockout spermatocytes, when compared to Spo11 −/− spermatocytes indicating that Hormad1 inhibits repair of exogenous DSBs in meiocytes 50 .…”
Section: Discussionmentioning
confidence: 89%
“…In order to determine whether the abnormal ©H2AX pattern was due to an increase in the number of DSBs or delayed repair, we assayed for homologous recombination repair markers like Replication Protein A (RPA32). The localization pattern and number of RPA foci on SC axis across meiotic stages are highly regulated and are used as bona-fide markers to assess repair kinetics/efficiency [47, 48]. We observed that while the numbers of RPA foci on autosomes in the early pachytene stage were similar in Sirt1 WT and Sirt1 Δmeio cells (Figs 4A and 4B), foci counts at late pachytene were 3-fold higher in Sirt1 Δmeio cells when compared to Sirt1 WT (Figs 4C and 4D).…”
Section: Resultsmentioning
confidence: 99%
“…In mice, NCOs are the prevalent outcome of the repair of programmed meiotic DSBs with the NCOs/COs overall ratio 9:1, based on cytological data and sperm typing 7,49,50 . Despite their prevalence and assumed functional significance for meiotic synapsis of homologous chromosomes 10,11,50 little is known about their genome-wide distribution and properties. In this study, we used whole-genome sequencing to detect and characterize a unique dataset of 95 NCO events in 10 mouse chromosomes using the B6.PWD-Chr # panel of mouse consomic strans.…”
Section: Discussionmentioning
confidence: 99%